Method of active correlations for DSSSD detector application - Tsyganov, Y S (arXiv.org, 2015)
Real-time PC based algorithm is developed for DSSSD ( Double Side Silicon Strip Detector) detector. Brief description of the detection system is also presented. Complete fusion nuclear reaction natYb+48Ca->217Th is used to test this algorithm at 48Ca beam. Example of successful application of a former algorithm for resistive strip PIPS detector is presented too.